1990
DOI: 10.1002/bjs.1800770425
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serosal invasion and free intraperitoneal cancer cells in gastric cancer

Abstract: Survival rates after curative gastrectomy for advanced gastric cancer among 238 patients in whom the cancer was invading the serosa were compared with 283 patients without serosal invasion. Generalized Wilcoxon estimates for 5-year survival rate were 47.1 per cent for patients exhibiting serosal invasion and 75.9 per cent for patients without serosal invasion. The frequency of lymph node metastasis increased proportionately with the extent of serosal invasion: 18.4 per cent in cases of S0; 53.8 per cent in cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
126
0
17

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(153 citation statements)
references
References 5 publications
10
126
0
17
Order By: Relevance
“…However, when the tumor invaded the serosa (pT3) and adjacent organs (pT4), the percentages of positive PWC were 19% and 73%, respectively. Previous studies also reported that serosal invasion was associated with a higher likelihood of cytological positivity [2,3,13,21,24]. It seems that the invasion of gastric serosa is a prerequisite for transperitoneal metastasis.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, when the tumor invaded the serosa (pT3) and adjacent organs (pT4), the percentages of positive PWC were 19% and 73%, respectively. Previous studies also reported that serosal invasion was associated with a higher likelihood of cytological positivity [2,3,13,21,24]. It seems that the invasion of gastric serosa is a prerequisite for transperitoneal metastasis.…”
Section: Discussionmentioning
confidence: 82%
“…Peritoneal recurrence is a common cause of death even after curative resection for gastric adenocarcinoma [1][2][3][4][5][6]. This is believed to be due to the presence of malignant cells that have already seeded at the time of operation but cannot be detected macroscopically.…”
Section: Introductionmentioning
confidence: 99%
“…While many patients who present with perforation are diagnosed with stage IV or non-curable disease, a significant number of patients with stage I-III disease may benefit from curative-intent resection. Spillage of tumor into the peritoneal cavity as a result of perforation was thought to carry a poor prognosis, similar to that of peritoneal disease [14,15]; however, several of the publications in this review argue that peritoneal contamination did not adversely affect survival in these patients [4,9,11].…”
Section: Discussionmentioning
confidence: 85%
“…However, by the conventional cytology, patients with negative cancer cells have occasionally developed recurrent peritoneal disease after surgery, which thus resulted in a low sensitivity of the cytology (Boku et al, 1990;Abe et al, 1995;Schofield et al, 1997;de Manzoni et al, 2006). Almost half of all patients with serosa-invading gastric carcinoma experience peritoneal recurrence even after a curative surgical resection (Martin et al, 2002;Tsuburaya et al, 2005).…”
mentioning
confidence: 99%